2021
DOI: 10.1002/star.202000217
|View full text |Cite
|
Sign up to set email alerts
|

α‐Amylase Immobilization on P(HEMA‐co‐PEGMA) Hydrogels: Preparation, Characterization, and Catalytic Investigation

Abstract: The aims of this study are to synthesize and characterize poly (2‐hydroxyethyl methacrylate‐co‐poly (ethylene glycol) methacrylate) (P(HEMA‐co‐PEG500MA)) structures containing polyethylene glycol (PEG) side groups and to investigate their possible use in α‐amylase immobilization. For this purpose, P(HEMA‐co‐PEG500MA) copolymer structures are synthesized by using different monomer ratios. P(HEMA‐co‐PEG500MA) copolymer structures are confirmed by Fourier transform infrared spectroscopy (FTIR), and elemental anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 47 publications
0
6
0
Order By: Relevance
“…In addition, there is a change in the intensity of absorption peaks due to the incorporation of oxygen-containing polar functional groups on the surface of 3D-printed PLA samples after APPJ treatment, such as carbonyl peaks (C=O), which represents surface oxidation [27,30,49]. The asymmetrical methyl bending (CH 3 ) peak of HEMA was discovered at 1520-1530 cm −1 after UV grafting with composite hydrogel; the ester groups were identified by a peak at C=O stretching at 1738 cm −1 and C-O stretching at 1280 cm −1 ; the alcoholic groups were identified by a peak at O-H bending at 1035 cm −1 and C-O stretching at 3465 cm −1 ; and the peak at 1642 cm −1 due to absorption indicates C=C methacrylate [37,43,44]. As for the PEGMA, its functional group ether linkage peak appears at 1115 cm −1 , the OH peak at 3610-3670 cm −1 , and the CH 2 peak at 2855 cm −1 [43,44].…”
Section: Ftir Characterization Of Surface-modified 3d-printed Pla Sam...mentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, there is a change in the intensity of absorption peaks due to the incorporation of oxygen-containing polar functional groups on the surface of 3D-printed PLA samples after APPJ treatment, such as carbonyl peaks (C=O), which represents surface oxidation [27,30,49]. The asymmetrical methyl bending (CH 3 ) peak of HEMA was discovered at 1520-1530 cm −1 after UV grafting with composite hydrogel; the ester groups were identified by a peak at C=O stretching at 1738 cm −1 and C-O stretching at 1280 cm −1 ; the alcoholic groups were identified by a peak at O-H bending at 1035 cm −1 and C-O stretching at 3465 cm −1 ; and the peak at 1642 cm −1 due to absorption indicates C=C methacrylate [37,43,44]. As for the PEGMA, its functional group ether linkage peak appears at 1115 cm −1 , the OH peak at 3610-3670 cm −1 , and the CH 2 peak at 2855 cm −1 [43,44].…”
Section: Ftir Characterization Of Surface-modified 3d-printed Pla Sam...mentioning
confidence: 99%
“…It is non-toxic, biocompatible, and insoluble after swelling in aqueous media [36,[41][42][43]. Poly(ethylene glycol) methacrylate (PEGMA) is a hydrophilic monomer with a special binding force for water molecules [42][43][44]. Because of its non-toxicity and non-immunogenicity, PEGMA grafting can increase the adhesion and reproduction of cells, thereby improving the biocompatibility of hydrogels [42][43][44][45].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…5,18,19 Owing to the improved stability, reusability, and high enzyme retention of the proposed supports, more and more types of materials have been used as supports to immobilize various enzymes. 20 To date, many carriers have been used for immobilization including natural 21−23 or synthetic polymers, 24 copolymers, 25 hydrogels, 26 beads, 27−29 blends, 30 nanofibers, 31−34 nanoparticles, 35−40 composites, 41−44 metal−organic frameworks, 45,46 etc. We refer readers to several recent review articles that comprehensively review these areas (method and support).…”
Section: Introductionmentioning
confidence: 99%
“…Conceptually, an immobilized enzyme can be defined as an enzyme that is physically confined or localized to a particular solid support, whose catalytic activities are maintained, and can be used repeatedly and continuously. , In scientific research, many methods of enzyme immobilization have been reported, including adsorption, covalent bonding, cross-linking, and entrapment; each has advantages and disadvantages. ,, Owing to the improved stability, reusability, and high enzyme retention of the proposed supports, more and more types of materials have been used as supports to immobilize various enzymes . To date, many carriers have been used for immobilization including natural or synthetic polymers, copolymers, hydrogels, beads, blends, nanofibers, nanoparticles, composites, metal–organic frameworks, , etc. We refer readers to several recent review articles that comprehensively review these areas (method and support). , Although the scientific literature is full of reports on new carrier supports and new approaches to immobilize enzymes, most of them are not even suitable for enzyme immobilization as the immobilization method and carrier used are insufficient to improve the enzyme properties of the matrix.…”
Section: Introductionmentioning
confidence: 99%